Mcmurray Test for Diagnosis of the Meniscal Tears - Alamgir Khan, Tauseef Raza, Muhammad Ovais, Junaid Ahmed Shahryar, Syed Abdur Rub Abidi, Usman Ali, Muhammad Siddique Karimi, Muhammad Inam (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: Meniscal tears are the most common injury of the knee. Tears of medial meniscus are seen more frequently as compared to lateral meniscus. Most often tears result from sports injuries where there is a twisting motion on the partially flexed, weight-bearing knee. As majority of our population resides in peripheries where access to arthroscopy and imaging modalities is difficult so we need a clinical test for evaluation of medial meniscal tears. And then this technique can be opted in our practice for early diagnosis of meniscal tears in order to take proper management for reducing morbidity of these particular patient, if its diagnostic accuracy comes out to high. Objective: To determine the diagnostic accuracy of McMurray test in diagnosing medial meniscal tears, taking arthroscopy as gold standard. Materials and Methods: This Cross-sectional validation study was carried out in Orthopedic Department of Medical Teaching Institute Lady Reading Hospital Peshawar from July 2021 to June 2023.In this study a total of 149 patients were observed. McMurray test was performed by the a single and same consultant and was looked for medial meniscal tear (present/absent).After this arthroscopy was done in each patient by the consultant orthopedic surgeon who has examined the patient and presence or absence of medial meniscal tear was noted. McMurray test results were compared with arthroscopy result. Results: In this study mean age was 30 years with SD ± 11.35. Eighty five percent patients were male and 15% patients were female. Diagnostic accuracy of MacMurray Test findings taking arthroscopy as gold standard was analyzed as the sensitivity was 76.55%, specificity was 75%, Positive predictive value was 99.10%, Negative predictive value was 8.10%. So, the overall diagnostic accuracy was 76.51%. Practical Implication: As in our setups majority of population resides in peripheries where access to arthroscopy and magnetic resonance imaging is difficult so there is a need of clinical test for diagnosing medial meniscal tears. And this technique can be opted in routine practice for early diagnosis of medial meniscal tears in order to take proper management for reducing morbidity of these particular patients after determining the sensitivity and specificity of the test. Conclusion: This study concludes that the McMurray test had sensitivity 76.55%, specificity 75%, Positive predictive value 99.10%, Negative predictive value 8.10% and the diagnostic accuracy 76.51% in diagnosis of meniscal tear keeping knee arthroscopy as gold standard. Keywords: Arthroscopy, Knee, McMurray test, Meniscal tear, Magnetic resonance imaging.